2022
DOI: 10.14812/cuefd.873723
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Teacher Qualities Perceived by Students and the Achievements of High and Low Socioeconomic Level Students

Abstract: Teacher qualities play a key role in students’ achievement. In general, however, disadvantaged students may not have as much opportunity to benefit from teacher support as advantaged students. Therefore, this study aims to find out the relationship between the teacher qualities and the achievements of high and low socioeconomic level students in math and science literacy, and reading. Data were obtained from the Program for International Student Assessment (PISA) 2018 results. The study is a quantitative analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
1
1
0
3
Order By: Relevance
“…While the perceived teacher support of Chinese students who participated in the PISA 2018 had a 5% effect on the reading literacy performance (Ma et al, 2021), it was a surprising finding that the teacher support did not contribute to the reading performance according to the perception of students from Türkiye (1‰). The same results were obtained in similar studies conducted with the PISA 2018 Türkiye sample (Büyükatak, 2022;İnci and Kaya, 2022).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…While the perceived teacher support of Chinese students who participated in the PISA 2018 had a 5% effect on the reading literacy performance (Ma et al, 2021), it was a surprising finding that the teacher support did not contribute to the reading performance according to the perception of students from Türkiye (1‰). The same results were obtained in similar studies conducted with the PISA 2018 Türkiye sample (Büyükatak, 2022;İnci and Kaya, 2022).…”
Section: Resultssupporting
confidence: 84%
“…Previous studies demonstrated the relationship of teacher support with reading literacy (İnci & Kaya, 2022;Büyükatak 2022;Radulovic et al, 2022;Chang & Bangsri, 2020;Chen et al, 2019;Ma et al, 2021;Mercer, 2011), first reading (Silinskas et al ., 2016), participation in reading (Zhao et al, 2018;Berman-Young, 2014), academic achievements other than reading (Bal, 2011;Chen, 2017;Klem & Connell, 2014;Ma et al, 2017), academic feelings (Lei et al, 2018), and attitude towards school (Ertem et al, 2021) from various perspectives.…”
Section: Motivation Sources For Reading and Teacher Supportmentioning
confidence: 98%
See 1 more Smart Citation
“…Hasta tal punto que, en algunos casos relacionados con el clima escolar y, encontrando el estudiante situaciones estresantes y/o problemáticas que afrontar en el mismo, los altos niveles de resiliencia no correlacionan con un mejor rendimiento académico. Esto se debe a que no son objeto del mismo grado de apoyo docente que el resto de sus compañeros por encontrarse en este tipo de situaciones desfavorables (Sibel y Kaya 2022).…”
Section: Conclusiones Y Discusiónunclassified
“…Como venimos denotando a lo largo del documento, los de mayor afección guardan relación con el clima escolar y lo que ello conlleva: prácticas educativas por parte del docente, grado de motivación al estudiantado, manejo del aula, expectativas hacia el logro e, incluso, el grado de trabajo docente en los propios factores personales del alumnado, tales como el auto concepto y la auto estima (Aydin y Erdem, 2022;Gabrielli et al, 2022;García-Crespo et al 2021;Sibel y Kaya, 2022).…”
Section: Conclusiones Y Discusiónunclassified